Structure and Function of Proteins Investigated By Crystallographic and Spectroscopic Time-Resolved Methods - (:unkn) unknown (My University, 2013)
Biomolecules play an essential role in performing the necessary functions for life. The goal of this thesis is to contribute to an understanding of how biological systems work on the molecular level. We used two biological systems, beef liver catalase (BLC) and photoactive yellow protein (PYP). BLC is a metalloprotein that protects living cells from the harmful effects of reactive oxygen species by converting H2O2 into water and oxygen. By binding nitric oxide (NO) to the catalase, a complex was generated that mimics the Cat-H2O2 adduct, a crucial intermediate in the reaction promoted by the catalase. The Cat-NO complex is obtained by using a convenient NO generator (1-(N,N-diethylamino)diazen-1-ium-1,2-diolate). Concentrations up to 100~200 mM are reached by using a specially designed glass cavity. With this glass apparatus and DEANO, sufficient NO occupation is achieved and structure determination of the catalase with NO bound to the heme iron becomes possible. Structural changes upon NO binding are minute. NO has a slightly bent geometry with respect to the heme normal, which results in a substantial overlap of the NO orbitals with the iron-porphyrin molecular orbitals. From the structure of the iron-NO complex, conclusions on the electronic properties of the heme iron can be drawn that ultimately lead to an insight into the catalytic properties of this enzyme. Enzyme kinetics is affected by additional parameters such as temperature and pH. Additionally, in crystallography, the absorbed X-ray dose may impair protein function. To address the effect of these parameters, we performed time-resolved crystallographic experiments on a model system, PYP. By collecting multiple time-series on PYP at increasing X-ray dose levels, we determined a kinetic dose limit up to which kinetically meaningful X-ray data sets can be collected. From this, we conclude that comprehensive time-series spanning up to 12 orders of magnitude in time can be collected from a single PYP crystal. Time-resolved X-ray data collected at pH's of 4, 7 and 9 demonstrate that pH alters the kinetics of the PYP photocycle dramatically. At pH 4 the photocycle lasts almost one order of magnitude longer in time compared to pH 7. The final intermediate that accumulates at both pH 7 and pH 4 is absent at pH 9. Results from the dose- and the pH-dependent time-resolved crystallographic experiments show that it is imperative to carefully control the conditions under which time-resolved data are collected. With these considerations we collected a comprehensive time-series from nanoseconds to seconds at 14 different temperature settings from -40 °C to 70 °C. Results from time-resolved crystallography are corroborated by employing time-resolved absorption spectroscopy. For this, absorption spectra on crystals and solution are collected by a fast micro-spectrophotometer custom-designed in our lab. We identify kinetic phases of the PYP photocycle at all 14 temperature settings. Relaxation times associated with these phases are temperature-dependent and can be fit by the Van't Hoff-Arrhenius equation. Kinetic modeling yields entropy and enthalpy values at the barriers of the activation solely from the time-resolved crystallographic data. With this, we advance crystallography to a new frontier: the determination of free energy surfaces. Investigating enzymatic reactions can be challenging, because they are non-cyclic. After one turnover product must be washed away and substrate must be reloaded. A promising approach for routine application can be envisioned at the new 4th generation X-ray sources, such as X-ray free electron lasers (XFELs). With our results we set the scene to comprehensively investigate all kinds of enzymatic reactions with these instruments.